High‐sensitivity cardiac troponin T for detection of subtle abnormalities of cardiac phenotype in a general population of elderly individuals. (28th December 2012) - Masson, S.; Latini, R.; Mureddu, G. F.; Agabiti, N.; Miceli, M.; Cesaroni, G.; Forastiere, F.; Wienhues‐Thelen, U.‐H.; Block, D.; Zaugg, C.; Vago, T.; Boccanelli, A.; et al.
Abstract Objective To investigate the association between circulating cardiac biomarkers and minor abnormalities in cardiac phenotype [left ventricular (LV) mass and midwall fractional shortening (MFS)] in elderly individuals in a general population sample. Design and setting We examined the relationship between plasma concentrations of high‐sensitivity cardiac troponin T (hs‐cTnT) or N‐terminal probrain natriuretic peptide (NT‐proBNP) and elevated LV mass (LV mass/body surface area >95 g m−2 for women and 115 g m−2 for men), reduced MFS (<15%) or isolated LV diastolic dysfunction in 1973 elderly subjects (mean age 73 ± 5 years, range 65–84) resident in the Lazio region of Italy and enrolled in the PREDICTOR study. Results Overall, 24.8% of subjects had elevated LV mass, and 30.4% had reduced MFS. Median [quartile 1–3] plasma concentrations of hs‐cTnT and NT‐proBNP were higher in individuals with elevated than those with normal LV mass: 6.6 [3.5–11.6] and 147 [64–296] ng L−1 vs. 4.6 [3.0–8.1] and 79 [41–151] ng L−1 respectively (P < 0.001). There was a graded increase in median hs‐cTnT concentrations across clinical categories of LV hypertrophy: 4.6 [3.0–8.1], 5.8 [3.1–10.2], 7.6 [3.8–13.7] and 8.4 [3.8–17.6] ng L−1 for subjects with normal LV mass and mild, moderate or severe LV hypertrophy respectively (P < 0.0001); hs‐cTnT also increased with increasing quartiles of MFS or grades of isolated LV diastolic dysfunction. Conclusions Within an extremely low range of concentrations, increased hs‐cTnT amongst community‐dwelling elderly subjects is associated with subtle alterations in cardiac phenotype, suggesting that minor injury to cardiac myocytes and subsequent release of troponin reflect subclinical pathophysiological LV deterioration in this population.